Application of 3D Printing Technology in the Mechanical Testing of Complex Structural Rock Masses. (13th October 2021) - Xia, Yingjie; Meng, Qingkun; Zhang, Chuanqing; Liu, Ning; Zhao, Zhenxing; Chen, Jun; Yang, Gao
Abstract : In the engineering of underground construction, the discontinuous structures in rock mass have important influences on the mechanical behaviors of the subsurface of rock mass. The acquisition of mechanical parameters is the basis of rock mass engineering design, construction, safety, and stability evaluation. However, the mechanical parameters and failure characteristics of the same rock mass under different mechanical conditions cannot be obtained due to the limitations of specimen preparation techniques. In recent years, with the continuous development of 3D printing (3DP) technology, it has been successfully applied to the repetitive preparation of rock mass samples. The combinations of 3DP and other techniques, such as 3D scanning and CT scanning, provided a new approach to study the mechanical behavior of complex structural rock masses. In this study, through a comprehensive review of the technical progress, equipment situation, application fields, and challenges of the use of 3DP technology, the following conclusions were obtained: (1) 3DP technology has advantages over traditional rock mass specimen preparation techniques, and the verification of test results using 3D printed samples shows that the 3DP has broad application prospects in geotechnical engineering. (2) The combination of 3DP and other advanced techniques can be used to achieve the accurate reconstruction of complex structural rock masses and to obtain the mechanical and failure characteristics of the same rock mass structure under different mechanical boundary conditions. (3) The development of 3DP materials with high strength, high brittleness, and low ductility has become the major bottleneck in the application of 3DP in geotechnical engineering. (4) 3D printers need to meet the high precision and large size requirements while also having high strength and long-term printing ability. The development of 3D printers that can print different types of materials is also an important aspect of the application of 3DP in geotechnical engineering.